2022
DOI: 10.1002/cbdv.202200916
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Active Constituents and Mechanisms of Semiliquidambar cathayensis Chang Roots against Rheumatoid Arthritis through Network Pharmacology, Molecular Docking, and in Vivo Experiment

Abstract: Semiliquidambar cathayensis Chang roots (SC) are traditional Chinese medicine for treating rheumatoid arthritis (RA). However, the effect and potential mechanism of SC remain unclear. This study aims to reveal the anti-RA constituents and mechanisms of SC based on network pharmacology, molecular docking, and adjuvantinduced arthritis (AIA) model rat experiment. In this work, 9 potential active constituents, including kaempferol, quercetin, naringenin, paeoniflorin, catechin, fraxin, gentianin, hesperetin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…41 There is a growing number of research papers that have used the network pharmacology to elucidate the mechanism of TCM in treatment of RA. [42][43][44][45] Therefore, in this work, we applied network pharmacology as well as molecular docking to predict and shed light on the potential molecular mechanisms of action of Mag on RA. The results showed that the intersection of Mag targets and RA targets contained 6 genes: ACHE, PXR, PTGS2, PTGS1, RXRA and CA2.…”
Section: Discussionmentioning
confidence: 99%
“…41 There is a growing number of research papers that have used the network pharmacology to elucidate the mechanism of TCM in treatment of RA. [42][43][44][45] Therefore, in this work, we applied network pharmacology as well as molecular docking to predict and shed light on the potential molecular mechanisms of action of Mag on RA. The results showed that the intersection of Mag targets and RA targets contained 6 genes: ACHE, PXR, PTGS2, PTGS1, RXRA and CA2.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a commonly regulated process of the host defense system in response to infections of tissue damage, harmful stimuli, physical stress, and others. [34,[46][47][48][49][50][51] Commonly, inflammation is closely related to BS, and inflammatory cytokine overexpression is accompanied by blood stasis. [10,52] In this study, LJ prominently reduced the levels of pro-inflammatory cytokines TNF-α, IL-6, and IL-8, while notably enhancing the anti-inflammatory cytokine IL-10 level compared with the model group.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a commonly regulated process of the host defense system in response to infections of tissue damage, harmful stimuli, physical stress, and others [34,46–51] . Commonly, inflammation is closely related to BS, and inflammatory cytokine overexpression is accompanied by blood stasis [10,52] .…”
Section: Methodsmentioning
confidence: 99%
“…TNF-α is increased in many pathological conditions, including sepsis, malignancy, heart failure, and chronic inflammatory diseases [ 30 , 31 ]. Increased TNF can be found in the blood and joints of patients with severe rheumatoid arthritis [ 32 ]. The level of TNF-α can directly reflect the degree of intestinal mucosal injury during intestinal I/R injury in rats.…”
Section: Discussionmentioning
confidence: 99%